Practical Clinical Research Design and Application A Primer for Physicians, Surgeons, and Clinical Healthcare Professionals - Fabricant, Peter D.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2024)
Every practicing physician, surgeon, advanced practice provider, and allied health professional interacts regularly with peer-reviewed literature: either while creating it, or consuming it. Despite the countless hours over many years spent in formal clinical training, many clinicians and clinician-authors lack advanced training or a working nuanced knowledge of research methodology and study design. Institutions have responded to this gap by reinforcing their ranks with statistical and methodological support in the form of data analysts, epidemiologists, and biostatisticians. However, clinicians are often unable to 2talk the methodological talk3 to guide them. This ultimately results in a stark disconnect between clinically relevant aspects of research and appropriate study design. Existing research methodology texts are largely written by statisticians, epidemiologists, and other academic public health experts. These are not easily digestible by practicing clinicians who need practical knowledge of this content to design their own research or enhance their understanding of the medical literature. Furthermore, these texts are often too detailed or 2in the weeds3 with regard to mathematics and statistical mechanics. Practical knowledge is not centrally located; rather, it is spread out among multiple books, articles, and other sources. This book is a concise, accessible, and practical guide for clinicians to read and reference when designing and reviewing clinical research. It is designed to be a standalone text, written 2by a clinician, for clinicians3 by a practicing clinical research expert who has had advanced formal training in research methodology, biostatistics, and epidemiology. Topics covered include descriptive and comparative statistics, power and sample size calculations, diagnostic tests, bias, and study design. In each chapter, consideration is given to study mechanics, advantages and disadvantages of each design, and illustrative analytical reviews of existing literature.
Part I: Foundational Basics -- Descriptive Statistics -- Comparative Statistics: Categorical Data -- Comparative Statistics: Continuous Data -- Statistical Power and Power Calculations -- Characteristics of a Diagnostic Test: Sensitivity, Specificity, Positive Predictive Value, and Negative Predictive Value -- Statistical Bias -- The Iterative Process of Designing Successful Clinical Research -- Part II: Choosing and Executing an Appropriate Clinical Study Design -- Randomized Controlled Trials -- Case-Control Studies -- Cohort Studies -- Cross-Sectional Studies -- Case Series and Case Reports -- Part III: Specialized Study Designs -- Propensity Score Matched Studies -- Interrater and Intrarater Reliability Studies -- Clinical Outcome Scale Development and Validation.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Medicine; Clinical medicine -- Research; Clinical Medicine; Clinical Research